2014
DOI: 10.1177/0018720814525629
|View full text |Cite
|
Sign up to set email alerts
|

On-the-Fly Scheduling as a Manifestation of Partial-Order Planning and Dynamic Task Values

Abstract: On-the-fly task scheduling is computationally tractable despite its surface complexity and understandable as an example of both the partial-order planning strategy and the dynamic-value approach to prioritization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The speeding up of service is triggered by the appearance of long customer queues. Hannah and Neal (2014) treated the decision process as a two-stage process with tasks selected for execution but then considered for either immediate execution or deferral until a later time depending on variables such as workload and time to deadline. Finally Kokkinou and Cranage (2011) used an online scenario-based survey to identify relevant variables and derived a regression equation for the choice between self-service or manual service in a hotel check-in process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The speeding up of service is triggered by the appearance of long customer queues. Hannah and Neal (2014) treated the decision process as a two-stage process with tasks selected for execution but then considered for either immediate execution or deferral until a later time depending on variables such as workload and time to deadline. Finally Kokkinou and Cranage (2011) used an online scenario-based survey to identify relevant variables and derived a regression equation for the choice between self-service or manual service in a hotel check-in process.…”
Section: Resultsmentioning
confidence: 99%
“…Within the literature review, Ilar (2008) judged an approach suggested (but not implemented) by Baines and Benedettini (2007) might be too complex to be industrially applicable and put forward a more straightforward method which in their view offers most of the advantages with much less effort. Hannah and Neal (2014) provided a highly simplified representation of the tasks undertaken by people but determine that the level of abstraction is appropriate for the aims of the study. This trade-off between meeting simulation study objectives against the cost and effort of doing may be resolved by adjusting the conceptual model specification in an iterative process until a feasible solution is found (Robinson, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, changes are taking place on this subject and the incorporation of human factors has become a major discussion among professionals from different areas of modeling and simulation, as reported by Cummings and Guerlain (2007), Bruzzone, Briano, Bocca, and Massei (2007), Hannah and Neal (2014) and Chen, et al (2016).…”
Section: Introductionmentioning
confidence: 99%